The historicization of theological concepts in the thought of Ignacio Ellacuría - Carrera U., Randall (2020)
This article explains Ignacio Ellacuría’s understanding of historization. It is proposed that historization is not limited to the elucidation of methodological criteriabut that it is the axis from which a new comprehension of methodological concepts derived from Latin America reality is allowed. The study begins with the explanation of some key categories to understanding Ellacuria’s thoughts, then later digs deeper into what the author develops about historicization by deconstructing his implications about Liberation Theology, his contribution to the elaboration of some fundamental theological concepts and his role as ideological critique. Some additional insights are offered related to Ellacuria´s contribution to the Latin American theological methodology. Keywords: Ignacio Ellacuría, Theology of liberation, Historicization of theology, Theological method